The Influence of Product Quality and After-Sales Service on Repurchase Intention of Wuling Brand Cars in Kolaka Regency: Pengaruh Kualitas Produk dan After Sales Service Terhadap Repurchase Intention Mobil Merek Wuling di Kabupaten Kolaka - Aljafar, Dapra; Ismanto; Stiadi, Muhammad (IAIN Kendari, 2026)
The purpose of this study is to analyze the influence of product quality and after-sales service on repurchase intention of Wuling brand cars in Kolaka Regency. This research is a survey research by collecting data through questionnaires. The population taken in this study were all Wuling car users in Kolaka Regency. The sampling technique used in this study was purposive sampling where the sampling technique was determined by determining certain criteria using the Hare formula, so that the number of samples in this study was 110 respondents in Kolaka Regency who used Wuling brand cars. The validity and reliability test of the research instrument used SPSS 25.0. Data analysis used SmartPLS 3.0 for the external model and structural model. The results of this study indicate that product quality influences the desire to repurchase intention. Then, the results of the study also showed that there was a positive and significant influence between after-sales service and repurchase intention.